Internal Barriers of Family Business: A Survey in Wood-Working and Furniture Family Enterprises in Slovakia before and During the COVID-19 Pandemic - Halasz, Martin; Sedliacikova, Mariana; Dobrovic, Jan; Janáková-Sujová, Andrea; Schmidtová, Jarmila (Journal of Ecohumanism, 2024)
Family businesses are an important part of any economy. As in many other industries, wood-working and furniture family businesses in Slovakia face barriers that affect their sustainability and competitiveness. On the one hand, there are external barriers, or determinants, whether macro-environments (political, legal, economic, demographic, socio-cultural, technological, informational, ecological) or micro-environments, such as customers, suppliers, intermediaries, competitors and the public. On the other hand, family businesses are no less influenced by internal barriers, which include management, finance, human resources, marketing, research and development, succession, generation change. In connection with the COVID-19 pandemic, these barriers have intensified. Our goal was to examine how wood-working and furniture family businesses in Slovakia perceive the importance of internal company barriers brought about by the pandemic. The main purpose of the research is to identify significant differences in internal barriers in the segment of family woodworking and furniture enterprises in Slovakia before and during the COVID-19 pandemic. To obtain relevant results, the study surveyed 443 family enterprises operating in wood-working and furniture industries. To meet the stated goal, the methodological tool of the research method was a questionnaire survey which addressed the family wood-working and furniture enterprises. The established hypotheses were tested using statistical methods: analysis of variance, Interval estimation of relative abundance, Duncan's post-hoc test. Based on the findings obtained by collecting and evaluating the questionnaire, it was concluded that the importance of individual internal barriers in family business varies with changing conditions. In particular, property succession, generational change was ranked among the most important barriers before the pandemic. With the advent of the pandemic, however, comes a change where the importance of all barriers has increased sharply and barriers such as marketing, finance, human resource management and management are at the forefront. The results of the paper are a contribution for science and practice and open up possibilities for further research in the sector of Slovak woodworking and furniture family businesses. Considering the specifics of family businesses in this context will allow for a deeper understanding of their responses to the pandemic and contributes to the formulation of recommendations and strategies to strengthen their resilience in times of crisis.